2017
DOI: 10.18632/oncotarget.20058
|View full text |Cite
|
Sign up to set email alerts
|

MiR-324-3p promotes tumor growth through targeting DACT1 and activation of Wnt/β-catenin pathway in hepatocellular carcinoma

Abstract: Recently, it has been reported that miR-324-3p participates in regulation of the carcinogenesis and tumor progression in various cancers. However, the expression and function of miR-324-3p in hepatocellular carcinoma (HCC) remain unclear. In the current study, miR-324-3p expression was significantly up-regulated in HCC tissues and cell lines. HCC patients with high miR-324-3p level showed poor prognostic features and shorter overall survival and disease-free survival. And in vitro and in vivo experiments revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 27 publications
3
34
0
Order By: Relevance
“…Previous studies have found that miRNAs promote HCC invasion and metastasis via the Wnt/β-catenin signaling pathway (28,29). The results of the present study demonstrated that overexpression of miR-2053 resulted in a reduction in Wnt3 protein levels.…”
Section: Mir-2053 Inhibits Activation Of the Wnt/β-catenin Signaling supporting
confidence: 67%
“…Previous studies have found that miRNAs promote HCC invasion and metastasis via the Wnt/β-catenin signaling pathway (28,29). The results of the present study demonstrated that overexpression of miR-2053 resulted in a reduction in Wnt3 protein levels.…”
Section: Mir-2053 Inhibits Activation Of the Wnt/β-catenin Signaling supporting
confidence: 67%
“…We did not observe a correlation between the number of potential target genes for a miRNA and the number of cohorts where it is predicted ( Figure S20). All these miRNAs are derived from precursors of already established oncomiRs or tumor suppressor miRNAs, or known to be involved in immune response or inflammation [50][51][52][53][54][55][56][57][58][59][60][61]. Note that hsa-miR-17-3p, hsa-miR-17-5p, hsa-miR-18a-3p, hsa-miR-18a-3p, hsa-miR-20a-3p, hsa-miR-20a-5p, and hsa-miR-92a-1-5p are part of a single miRNA cluster on chromosome 13 and this polycistronic cluster (known as miR-17-92) is well known to be composed of oncomiRs involved in proliferation and tumor angiogenesis, and reducing apoptosis of cancer cells [50].…”
Section: Combining Transcriptional and Post-transcriptional Regulatiomentioning
confidence: 99%
“…72 Strand selection is mainly determined by two rules involving 73 thermodynamic characteristics and 5 ′ nucleotide identity of a miRNA 74 duplex. The crystal structures of human AGO and its homologues have 75 highlighted a key role of a basic pocket of the MID domain that interacts 76 with the mono-phosphorylated 5 ′ end of the guide strand ( Thermodynamically unstable 5 ′ ends would be more readily accessible 79 to the pocket, leading to the preference for unstable 5 ′ ends by AGO 80 (Khvorova et al, 2003;Schwarz et al, 2003). Furthermore, analyses of 81 4/51 miRNA sequences indicated that there is a clear bias for U or A at the 5 ′ 82…”
Section: Introductionmentioning
confidence: 99%